Effect of Bio Formulations on Growth and Yield Parameters of Centella asiatica L., Cultivated in Hydroponic and Field Systems: A Comparative Study - Belwadi, Suheba; Holeyache, Adavesh Basavanneppa; Biju, Sreelekshmi (Asian Journal of Biological and Life Sciences, 2025)
Background: C. asiatica L is a perennial flowering herb from the Apiaceae family having high demand in Ayurveda and traditional medicine used to treat a variety of health conditions. This study evaluates the effects of bio formulations like Kunap Jala mentioned in Vrukshayurveda and Vermiwash, on growth and yield characteristics of C. asiatica L. grown by conventional field cultivation method against hydroponic system. Materials and Methods: Study consisted of two groups of Centella asiatica L.-Field cultivation and Hydroponic cultivation. Based on intervention each group again has two subgroups-Kunap Jala and Vermi wash, with 40 samples in each group. Standard package of practice was followed for field cultivation. For Hydroponic group, Nutrient Film Technique system was established with nutrient media. pH maintained at neutral and Total Dissolved Solvents maintained between 1000-1200 ppm. Results: Analysis of Bio formulations of Centella asiatica showed higher nutrients in Kunap Jala in comparison to Vermi wash. In comparison with field group and hydroponics group, field group had better yield; more specifically treatment with Kunapajala showed improved result than Vermi wash Conclusion: Both Kunap Jala groups on field and hydroponic method yielded better results than Vermi wash group, which may be due to higher nutrient percentage of Kunap Jala. Field system showed better results than Hydroponic system.
Keywords: Bio Formulations; Centella asiatica L.; Hydroponic system; Vrukshayurveda